Quantum‐Matter Bi/TiO2 Heterostructure Embedded in N‐Doped Porous Carbon Nanosheets for Enhanced Sodium Storage. Issue 4 (29th December 2020) - Huang, Man; Xi, Baojuan; Shi, Nianxiang; Feng, Jinkui; Qian, Yitai; Xue, Dongfeng; Xiong, Shenglin
Abstract : Combining the strength of heterostructure engineering with the properties of quantum materials, quantum‐scale heterostructure will open up a new stage for material design. Herein, a kind of anode material with heterostructures made of Bi/TiO2 quantum dots embedded into N‐doped carbon nanosheets (Bi/TiO2 HQDs⊂NC) is reported. Importantly, unique electronic states, structural distortions and defects, and functionalities can be integrated in the quantum‐scale heterostructure, giving rise to opportunities for reducing the ion‐diffusion resistance and facilitating interfacial charge transport at interface during the storage process. The integrated design greatly reduces the migration energy barrier of Na +, promotes the electron/Na + transportation, buffers the volume variation of electrodes upon cycling, heightens the electric conductivity and electrochemical reactivity of the hybrids, and provides rich active interfacial sites for sodium uptake. Due to these merits, these Bi/TiO2 HQDs⊂NC hybrid nanosheets manifest excellent sodium storage properties in terms of a high reversible capacity of 299.1 at 0.2 A g −1 with an ultrahigh rate capability up to 20 A g −1 with a capacity of 132.7 mAh g −1 and an ultralong cycle life over 10 000 cycles. Abstract : A hierarchical 2D hybrid nanosheet composed of bismuth/titanium dioxide heterostructure quantum dots embedded into N‐doped carbon nanosheets (Bi/TiO2 HQDs⊂NC) is designed and fabricated by a self‐template and in situ recrystallization‐self‐assembly strategy. Due to this novel and unique architecture design, the 2D hybrid electrode indicates excellent electrochemical performance as anode materials for sodium‐ion batteries.